Anatomic Variation of Subclavian Artery Visualized on Ultrasound-Guided Supraclavicular Brachial Plexus Block - Santvana Kohli; Naveen Yadav; Arunima Prasad; Sumantra Sarathi Banerjee (Case Reports in Medicine)
Use of ultrasonography for performance of nerve and plexus blocks has made the process simpler and safer. However, at times, variant anatomy of the visualized structures can lead to failure of blocks or complications such as intravascular injections. This is especially true in case of novice operators. We report a case of a variant branch of subclavian artery, possibly the dorsal scapular artery passing through the brachial plexus nerve bundles in the supraclavicular area. Since this variation in anatomy was visualized in the scout scan prior to the performance of the block, it was possible to avoid any accidental puncture. Hence, a thorough knowledge of the ultrasound anatomy is important in order to identify various aberrations and variations. It is also prudent to perform a preliminary scan, prior to performance of the block to localize the target area and avoid any inadvertent complications.